Oligoclonal bands and kappa free light chains: Competing parameters or complementary biomarkers? - Konen, Franz Felix; Wurster, Ulrich; Schwenkenbecher, Philipp; Gerritzen, Andreas; Groß, Catharina Christiane; Eichhorn, Peter; Harrer, Andrea; Isenmann, Stefan; Lewczuk, Piotr; Lewerenz, Jan; Leypoldt, Frank; Otto, Markus; et al. (Autoimmunity reviews, 2025)
Background: The 2024-revised McDonald criteria for multiple sclerosis (MS) proposed to incorporate cerebrospinal fluid (CSF)-specific oligoclonal bands and kappa free light chains (KFLC) as diagnostic biomarkers. While the 2017-revised criteria highlighted CSF-specific oligoclonal bands to indicate intrathecal IgG synthesis, significantly enhancing early MS diagnosis, KFLC have emerged as additional marker. Now, the question rises of whether both biomarkers serve as competing or complementary tools in MS diagnostics. Methods: In this narrative review, we extensively searched the literature on oligoclonal bands and KFLC determination in CSF and serum across neurological disorders, with a focus on MS, using the PubMed database to demonstrate the complementarity of both biomarkers. Results: Oligoclonal bands have long been a reliable marker of intrathecal IgG synthesis in MS, valued for their high diagnostic sensitivity, unique patient “fingerprints,” clonality differentiation, semi-quantitative analysis, and pre-analytic robustness. However, they present challenges in standardization, labor-intensity, method variability, examiner dependency, and limited data on non-IgG immunoglobulins. Quantitative KFLC measurement provides rapid, examiner-independent, and cost-effective assessment across all immunoglobulin classes but might have lower specificity, lacked consensus on standardized interpretation in recent years, and is not yet supported by comprehensive prospective multinational studies on its prognostic role. Conclusion: Both oligoclonal bands and KFLC have unique strengths and limitations that complement each other, potentially serving as complementary markers for evaluating intrathecal Ig synthesis in MS diagnosis. Further evidence is needed to establish the value of KFLC in MS diagnosis, thus multicenter prospective studies are being conducted to compare the diagnostic utility of both markers.